KONSTRUKSI PESAN DAKWAH PADA IKLAN RAMAYANA EDISI ROMADHAN 1438 H - Imam Safi'i (Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Da'wah can also be inserted into advertisements, in the form of good religious and moral teachings, such as various advertisements that often appear in various memorials of Islamic holidays, Ramayana ads for Romadhan 1438 H edition for example in this ad not only display the product's hard selling but also the effect or impact big and positive lifting the brand name itself. This Ramayana advertisement was just published on You Tube on May 26, 2017 but, the Views up to now have reached more than 3 million, is an achievement that can only take a few days. The results showed that 1) the construction of da'wah messages in the Ramayana ad edition of Romadhan 1438 H In the construct of the message preaching this ad used William Gimson's discourse analysis based on the three Core Frame categories: the central idea of ​​Advertising, Framing Devices: Framing Devices and Appeals to principle: the basic premise of the Central Idea (Core Frame) on the Romadhan 1438 H edition of Ramayana Ad that is about